2022
DOI: 10.1111/ina.13001
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of SARS‐CoV‐2 in air surrounding COVID‐19‐infected individuals with mild symptoms

Abstract: Since the beginning of the pandemic, the transmission modes of SARS‐CoV‐2—particularly the role of aerosol transmission—have been much debated. Accumulating evidence suggests that SARS‐CoV‐2 can be transmitted by aerosols, and not only via larger respiratory droplets. In this study, we quantified SARS‐CoV‐2 in air surrounding 14 test subjects in a controlled setting. All subjects had SARS‐CoV‐2 infection confirmed by a recent positive PCR test and had mild symptoms when included in the study. RT‐PCR and cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Although early studies at times proposed that SARS‐CoV‐2 was sparsely found in the patient environment, the ubiquity of the environmental presence of the virus in contiguity to the infected patient soon became more obvious 1 . There has been a plethora of investigations since that corroborate the common environmental presence at least of viral RNA 19–36 . These positive determinations have included caregiver garments and accessories.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although early studies at times proposed that SARS‐CoV‐2 was sparsely found in the patient environment, the ubiquity of the environmental presence of the virus in contiguity to the infected patient soon became more obvious 1 . There has been a plethora of investigations since that corroborate the common environmental presence at least of viral RNA 19–36 . These positive determinations have included caregiver garments and accessories.…”
Section: Introductionmentioning
confidence: 99%
“…The contamination of environmental and other touch surfaces with virus may occur directly or through settling from aerosol distribution. Evidence for potential aerosol distribution continues to emerge, but the consensus suggests that viral particles, as measured mainly through RNA detection, do circulate in air with variable distributions, within variable sizes of air particles, and for varied distances 20,22,24,26,28,30,32,33,35,37,52–56 . Few of these studies have examined for viable virus, but for those that had, positivity was determined, although for few samples 25,30,33,53,55 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations